The Life and Work of W. B. Nickerson (1865-1926) : Scientific Archaeology in Central North America - Dyck, Ian G (Book collections on Project MUSE., 2016)
"William Baker Nickerson was among the first in North America to receive formal training in archaeology. He investigated sites from New England to the Midwest and into the Canadian Prairies. In the course of exploration, he created an elegant and detailed record of discoveries and developed methods which later archeologists recognized as being ahead of their time. His life story spans the transition of North American archaeology from museums and historical societies to universities, throwing light on a phase of history that is little known."--